Preservation of maritime archaeology and underwater cultural heritage in Malaysia: a review - Nik Nurhalida Nik Hariry; Nor Aeini Haji Mokhtar (Penerbit Universiti Kebangsaan Malaysia, 2024)
Maritime archaeology and underwater cultural heritage are crucial for revealing a valuable collection of historical, and cultural importance submerged beneath Malaysia’s coastal waters. This paper comprehensively reviews the preservation efforts concerning Malaysia’s maritime archaeology and underwater cultural heritage. Malaysia has a vast coastline and a significant historical background in the maritime trade, resulting in a wide range of submerged archaeological sites dating back several centuries. Furthermore, the paper discusses the terms of maritime archaeology and underwater cultural heritage, the element of the term underwater cultural heritage, the law in Malaysia related to underwater cultural heritage, and the process of excavation of shipwrecks also artifacts in Malaysia's Waters. This review seeks to educate policymakers, academicians, researchers, and heritage practitioners about the significance of conserving Malaysia’s maritime archaeology and underwater cultural heritage by combining the existing research and practical experiences. It promotes increased awareness, funding, and coordinated actions to protect these invaluable connections to Malaysia’s maritime history for future generations.